First Stereo Selective Total Synthesis of Antimicrobial Trichoderic acid. Issue 15 (30th September 2016) - Kumar, Nandigama Satish; Kumar, Rayala Naveen; Rao, L. Chandrasekhara; Meshram, Harshadas Mitaram
Abstract: The first stereo selective total synthesis of the antimicrobial sesquiterpene trichoderic acid is reported. The key steps of this synthetic strategy involves ( R )‐CBS‐mediated stereoselective keto reduction, Horner–Wadsworth–Emmons (HWE) olefination was employed twice for chain elongation, requisite aldehyde to perform HWE olefination was prepared from commercially available 3‐methylcyclohexenone and intramolecular oxa Michael addition. Abstract : The first stereo selective total synthesis of the antimicrobial sesquiterpene trichoderic acid is reported. The key steps of this synthetic strategy involves ( R )‐CBS‐mediated stereoselective keto reduction, Horner–Wadsworth–Emmons (HWE) olefination was employed twice for chain elongation, requisite aldehyde to perform HWE olefination was prepared from commercially available 3‐methylcyclohexenone and intramolecular oxa Michael addition.